Models of Guidance needed for the Fundamental Transformation of Education - mohamad reza tamasoki (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2020)
Abstract Documents which are set for the fundamental transformation of the education system in Iran discuss only three counseling models, including educational, vocational and agreement types; and they neglect guidance models generally, let alone indigenous ones, in particular. Applying three proposed models do not lead into achieving all the objectives of the documents and there is a serious need to models appropriate for reaching all the documents goals and perspectives. Furthermore, while only guidance makes prevention possible, it needs executive models, proper structure and organization and duty description for all the school personnel. This article is a response to required guidance models for the fundamental transformation of the education system, and is the result of two previous researches done under the title of “guidance content analysis in Quran” and “qualitative theme analysis of triple documents”. Through six innovative models which are introduced here, ten previous common models are criticized and their differences and commonalities are revealed. Three of the ten are among consultant models which should be applied only by the consultant of the school; the rest overlap six innovative models, encompassing "Knowledge, Faith and Good Practice", "Insight", "Access to the Hidden Truth", "Justification", "Judgment" and "Spiritual Guidance", altogether, in spite of some differences. By the six proposed models, students might enjoy school attendance and reach their full potential. Keywords: Model, Guidance, Quran, Basics of the Documents for Transformation in Education System